Response of Cow Manure Dosage and KCl Fertilizer on Growth and Yield of Young Fruit of Okra (Abelmoschus esculentus L) Plants - Agus Hariadi Cipta Saputra; Luh Kartini; Made Sri Yuliartini (Warmadewa University Press, 2019)
This study aims to determine the effect of cow manure and KCl fertilizer and their interaction on the growth and yield of okra (Abelmoschus esculentus L.). This research was conducted in Sumerta Village, East Denpasar Sub-district, Denpasar city from March to June 2018. The design used in this study was a Randomized Block Design (RBD) consisting of 2 factors, namely Treatment of cow manure dosage consists of 3 levels, namely: K1 (10 Tons ha-1), K2 (20 Tons ha-1) and K3 (30 Tons ha-1). Whereas treatment of KCl Fertilizer dosage consists of 4 levels, namely: M0 (0 kg ha-1), M1 (50 kg ha-1), M2 (100 kg ha-1) and M3 (150 kg ha-1). The results show that the highest fresh weight of fruit per plant was obtained at a dose of cow manure 30 Tons ha-1 (K3) 309.32 g, which was not significant with a dose of cow manure 20 Tons ha-1 (K2) 296.05 g, an increase of 35.08% and 29.44% when compared to the fresh weight of fruit per plant obtained in the treatment dose of cow manure 10 Tons ha-1 (K1) 228.98 g. The highest fresh weight of fruit per plant at a dose of KCl fertilizer 150 kg ha-1 (M3) 299.97 g was not significant with all other KCl fertilizer doses, increased by 18.37%, 11.64% and 8.98% when compared to the lowest fresh weight of fruit per plant at a dose of KCl 50 kg fertilizer ha-1 (M1) 253.41 g.